“Perancangan Aplikasi Pariwisata Interaktif Kabupaten Simalungun Berbasis Multimedia Home Platform (MHP) pada Siaran Televisi Digital” - Syaipuddin; Juni Ismail (STKIP Subang, 2026)
Television is an important electronic medium for delivering information and entertainment to the public. However, analog television broadcasting has limitations, particularly in terms of interactivity and multimedia content. With the development of digital broadcasting technology, television services can now provide interactive multimedia content for viewers. This study aims to develop interactive multimedia content for digital television using middleware, specifically the Icareus iTV Suite. The Icareus iTV Suite is used to develop interactive multimedia applications that can be accessed directly through home television. The results show that the developed application can enhance viewer interaction and provide various multimedia features that are easily accessible through digital television.